Cochinchine française Excursions et reconnaissances. - French Indochina (Saigon [etc.] : Imprimerie du gouvernement [etc.], 1879)
"Dictionnaire stieng; recueil de 2,500 mots... par H. Azémar" v. 12, p. [99]-146. [251]-340.
Vol. 1-4, parts 1-8 (originally parts 1-12) were reissued 1891-1897.
Mode of access: Internet.
"No. 33 was issued as an official publication of French Indo-China"